Nail changes with chemotherapeutic agents and targeted therapies - Shankila Mittal; Niti Khunger; Satya Pal Kataria (Wolters Kluwer Medknow Publications, 2022)
Patients on Cancer chemotherapeutic agents often develop nail changes most of which are only cosmetic concern and disappear on drug withdrawal. But some nail changes can be painful and disabling thereby affecting quality of life substantially. Different components of the nail unit include the nail matrix, nail bed, nail plate, the hyponychium, lunula, the proximal and lateral nail folds. In this article we review the nail changes induced by chemotherapeutics and targeted anticancer drugs, preventive measures and treatment options available.